Approximate analytical mathods for solving ordinary differential equations - Radhika, T. S. L., 1974- author; Iyengar, T. K. V. author; Rani, T. Raja, 1972- author (Boca Raton, FL : CRC Press/Taylor & Francis)
Includes bibliographical references and index.